Planning, regulation and space standards in England: from 'homes for heroes' to 'slums of the future'. Issue 5 (1st September 2021) - Clifford, Ben; Ferm, Jessica
Abstract : The regulation of housing quality has a long history in England. As the state itself increasingly became a housing developer in the twentieth century, design standards were subject to self-regulation. Through this, the idea that housing quality includes minimum dwelling sizes – space standards – has entered public consciousness. The 2010–2015 coalition government introduced suggested space standards through planning control, but also extended the range of 'permitted development' – a form of deregulation – where space standards could not be applied. In this paper we explore the history of space standards in England and what these tell us about planning regulation.